The effect of starting position on elite swim start performance using an angled kick plate - Honda, K.; Sinclair, P.; Mason, B.; Pease, D. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The addition of a new start block in competitive swimming, the OSB11 with incline (kick) plate, has led to the development of a new starting technique, the kick start. Although some swimmers have limited access to these blocks, their approach to using it may determine their level of success. The purpose of this study was to a) determine the effect of kick plate position on the performance of the start and b) determine the effect on start performance of changing the swimmers position on the block prior to the start signal. Eighteen elite swimmers completed 30 `dive and glide` starts using the kick start in three different kick plate positions along with three variations in their weight. There was no effect of kick plate position on time. Leaning further towards the rear of the block resulted in higher velocity off the block however no significant difference in time to 7.5 m was seen.